PENGEMBANGAN MEDIA LUDO PINTAR UNTUK MENINGKATKAN KETERAMPILAN SOSIAL SISWA KELAS IV PADA MATERI KEKAYAAN BUDAYA INDONESIA DI MIS AL-IKHLAS NAGA TIMBUL - Abdul Gani Jamora Nasution; Rabiatul Adawiyah Batubara (Al-Ikram : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This research aims to develop Smart Ludo as a learning medium designed to enhance the social skills of fourth-grade students in the topic of Indonesian Cultural Heritage at MIS Al-Ikhlas Naga Timbul. The research method adapted the ADDIE development model, which consists of five stages: Analyze, Design, Development, Implementation, and Evaluation. The research instruments included validation sheets for material and media experts, practicality questionnaires for teachers and students, and learning achievement tests in the form of pretests and posttests. The research findings show that the feasibility level of the media, based on the assessment of the material expert, reached 90%, and the media expert assessment reached 92.5%, both of which fall into the very valid category. The practicality of the media, according to the teacher, scored 91% very practical, while the student assessment was 89.5% practical. The effectiveness of the media was reflected in the increase in students’ average scores from 63.33 in the pretest to 85.95 in the posttest, with an N-Gain value of 0.61, categorized as medium to high. Observations and interviews during the learning process showed that students became more enthusiastic, actively engaged in discussions, and demonstrated better teamwork skills. Teachers also noted that the use of this medium successfully created active, interactive, and enjoyable learning experiences. Therefore, Smart Ludo is proven to be feasible, practical, and effective for use in teaching Indonesian Cultural Heritage material, while contributing positively to improving students’ social skills.